(untitled) (Pedagogical Horizons, 2025)
Democracy is the foundation of our European society and culture of values. The promotion of democracy and the teaching of fundamental democratic principles and values begins at school at the latest. Learning about democracy and political education are, in a sense, constitutive prerequisites for a functioning democracy, because democratic competence, political maturity and the ability to make judgements do not develop on their own. In modern and complex media societies, democracy education is needed more than ever. This highlights the great importance of political education, knowledge transfer and the anchoring of democratic attitudes. Political education also includes spiritual national defence, which, according to the Federal Constitution (Art. 9a), is part of comprehensive national defence. The content relates to democratic values and awareness of neutrality, state sovereignty, democratic freedoms and human rights. This article examines the extent to which political and democratic education can be supported by further training measures. These questions were explored using the example of the university course ‘Understanding democracy in the context of spiritual national defence’, which was offered for the first time by the PHDL in cooperation with the Austrian Armed Forces in the 2024/2025 academic year. The survey of experts from the PHDL and the Austrian Armed Forces regarding this course revealed a consistent picture: Both the educational field and the military consider a high level of political education, democracy education and awareness-raising to be essential with regard to our national sovereignty and neutrality as well as human rights and peace education in general, albeit with different emphases. In today’s digitalised information society – with external threats as well as fake news and undemocratic tendencies from within – political education is more important than ever in every respect.